Traditional utilization, botany, phytochemistry, pharmacology, pharmaceutical analysis, processing and application of the seeds of Herpetospermum pedunculosum (Ser.) C.B. Clarke: a comprehensive review - Jiang, Zhixia; Zhang, Chuang; Yu, Xinran; Wang, Kaiyi; Sang, Zhenqi; Gong, Wan; Zhang, Qiaoyan; Meng, Xiongyu; Qin, Lupin; Zhao, Qiming (Frontiers in Pharmacology, 2024)
The seed of Herpetospermum pedunculosum (Ser.) C.B. Clarke, known in Chinese as Bo-Leng-Gua-Zi and in Tibetan as Sejimedo, are here abbreviated as H. pedunculosum seeds. H. pedunculosum seeds is a traditional Chinese medicine for protecting the liver, clearing heat, and detoxifying. A total of 125 chemical metabolites of H. pedunculosum seeds are found, including lignans, fatty acids, terpenes, coumarins, and others. The pharmacological activities of H. pedunculosum seeds are mainly in hepatoprotective, antioxidant, anti-cancer cells, and anticholestatic effects. In clinical application, it is mainly used in combination with other traditional Chinese medicines to play a key role in treating the liver disease. This paper gives a systematic review of above research aspects, proposes the potential limitations and put forward plausible solutions. Relevant literatures were searched in PubMed, Web of Science and Chinese National Knowledge Infrastructure with Herpetospermum as the key word. A number of studies have shown that H. pedunculosum seeds exert excellent hepatoprotective effects by acting on NF-κB, TGF-β, and Keap1-Nrf2 signaling pathways, which provide a solid base for its clinic application. However, more research is needed to explore the standard cultivation and quality evaluation of H. pedunculosum seeds and systematical structure-activity relationship of its active metabolites.